Pengembangan Media ESKIPAS Berbasis Augmented Reality Materi Sistem Pernapasan Pada Manusia untuk Meningkatkan Kolaborasi Siswa Kelas V SD - Ulimmachkrisa Salsabila Salwa Darin; Choirul Huda; Ferina Agustini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
A research has been successfully carried out on the development of Augmented Reality-based ESKIPAS media on human respiratory system materials to increase the collaboration of grade V students of SD Negeri Winong 01. This research is motivated by the low collaboration ability of students due to conventional learning that is less interactive. The method used is Research and Development (R&D) with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects amounted to 24 students of class V. The instruments used included interviews, observations, validation questionnaires of media experts and material experts, as well as questionnaires of teacher and student responses. The results of the study showed a very high level of validity with an average percentage of media experts of 87.95% and material experts of 90% (very valid category). The reliability test obtained a score of 98.5% for media validators and 94.5% for material validators (≥75%), so that it was declared reliable. The feasibility and practicality test showed a teacher response of 96.3% and a student response of 96.06% (very feasible category). The implementation of the media showed an increase in student collaboration by 27.27% from phase I to phase II. Thus, ESKIPAS media is valid, reliable, feasible, and effective in increasing student collaboration.